Analysis of the genes and mechanisms responsible for the cytotoxicity of the Legionella Ofk308 strain in the Tetrahymena host - Vidayanti, Istiana Nur; Watanabe, Kenta; Fujino, Ema; Shimizu, Takashi; Watarai, Masahisa (Frontiers in Microbiology, 2025)
BackgroundLegionella pneumophila, an intracellular pathogen responsible for the pneumonia-like Legionnaires’ disease in humans, inhabits aquatic environments, including man-made water systems such as water fountains, foot spas, and tap water, and exists as part of biofilms or as a protozoan parasite. As a bacterivore, Tetrahymena thermophila provides a favorable environment for Legionella to establish a replicative niche (Legionella-containing vacuole; LCV) under environmental stress. Conversely, the L. pneumophila Ofk308 strain, isolated from an Ashiyu foot spa, has been found to be cytotoxic to the ciliate T. thermophila CU427. This study aimed to identify the cytotoxicity-related genes of Legionella and elucidate their mechanisms specific to the Tetrahymena host.MethodsA comparative analysis using RNA-sequencing was conducted with two Legionella strains, Philadelphia-1 and Ofk308, to select several candidate genes. Deletion mutants of Ofk308 were constructed by homologous recombination. Eight out of ten candidate gene deletion mutants were successfully generated. These mutants were analyzed for cytotoxicity against T. thermophila and intracellular bacterial growth at 2 h, 24 h, and 48 h postinfection.Results and DiscussionsAmong the deletion mutants, Δ vicinal oxygen chelate (VOC) and msrB/A exhibited reduced cytotoxicity. Furthermore, LCVs formed in T. thermophila infected with DVOC and msrB/A were smaller in size compared to those formed by the parental strain Ofk308, suggesting a role in both cytotoxicity and intracellular growth. Multiple factors contribute to the cytotoxicity exhibited by the Ofk308 strain in protozoan host cells, and gene expression analysis may reveal additional relevant factors.